Long-term Deflections of Hybrid GFRP/Steel Reinforced Concrete Beams under Sustained Loads - Duy Nguyen, Phan; Hiep Dang, Vu; Anh Vu, Ngoc; Eduardovich, Polikutin Aleksei (Civil Engineering Journal, 2020)
One of the solutions to improve the flexural behavior of Glass fiber reinforced polymer (GFRP) reinforced concrete (RC) beams is the addition of tensile longitudinal steel reinforcement. The numerous studies to date on hybrid GFRP/steel RC elements have mainly focused on the static and short-term responses, very little work has been done regarding the long-term performance. This paper presents experimental results of time-dependent deflections of cracked GFRP and hybrid GFRP/steel RC beams during a 330-day-period in natural climate conditions. Three hybrid GFRP/steel and one GFRP RC beams with dimensions 100Ã—200Ã—2000 mm were tested in four-point bending. Different steel reinforcement ratios were used to evaluate the effect of the steel reinforcement on the long-term behavior of the beams. Experimental results show that the immediate deflections are inversely proportional to the additional steel reinforcement. With the same initial instantaneous deflection, the total deflection increases when increasing the steel reinforcement ratio. Also, temperature (T) and relative humidity (RH) significantly affect the long-term deflection of the tested beams. The measured long-term deflections were found to be in good agreement with the theoretical values calculated from the proposed method. However, there was an overestimation when using ACI 440.1R-15 or CSA-S806-12 procedures.